Schistocerca piceifrons piceifrons (Orthoptera: Acrididae) as a Source of Compounds of Biotechnological and Nutritional Interest. Issue 5 (13th October 2019) - Pérez-Ramírez, Rogelio; Torres-Castillo, Jorge Ariel; Barrientos-Lozano, Ludivina; Almaguer-Sierra, Pedro; Torres-Acosta, Reyna Ivonne
Abstract: The Central American locust, Schistocerca piceifrons piceifrons (Walker) is a major agricultural pest in Mexico and Central America. Control measures against this pest have generated much environmental damage and substantial financial costs because chemical insecticides are used. Yet various Orthoptera species also appear to be a potential source of nutrients and a source of bioactive metabolites. Here, we studied the presence of secondary metabolites in the adult stage of S. p. piceifrons by applying different colorimetric techniques. Adults were collected from the southern region of Tamaulipas, Mexico, during September–December 2017. These samples were subjected to sequential processes of eviscerating, drying, pulverizing, extracting, and detecting of metabolites. Extractions were carried out in water, 50% ethanol, and absolute ethanol. The presence of phenolic compounds, alkaloids, tannins, saponins, flavonoids, and quantity of antioxidants against the DPPH (2, 2-diphenyl-1-picrylhydrazyl) and ABTS (2, 2′-azino-bis, 3-ethylbenzothiazoline-6-sulfonic acid) radicals were determined and reported. Proximate analysis showed that S. p. piceifrons has a high protein content (80.26%), low fat content (6.21%), and fiber content (12.56%) similar to other Orthoptera species. Chitin and chitosan contents of S. p. piceifrons were 11.88 and 9.11%, respectively; the recovery percentage of chitosan from chitin was 76.71%. Among the Orthoptera, the protein content of this pest is among the highest while its contents of chitin and chitosan are similar to those of other insect species (e.g., Bombix mori Linnaeus [Lepidoptera: Bombycidae]). Our results suggest this pest species is a potential source of bioactive compounds of biotechnological interest for use by pharmaceutical and food industries.